UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN PROBING- PROMPTING PADA SISWA KELAS X KULIT A SMK NEGERI 5 YOGYAKARTA - Subyanto Dwi Santoso; Pardimin Pardimin; sri adi widodo (Universitas Sarjanawiyata Tamansiswa, 2014)
the purpose of this study is to describe the process of implementing probing-prompting learning model in order to increase students activities and achievements in learning mathematic especially students in 10th grade of Kulit A SMKN 5 Yogyakarta. The subjects of this research were thirty students in 10th grade of Kulit A SMKN 5 Yogyakarta. The research applies the classroom action research that was implemented at least in two cycles. Based of the results in this study were concluded that implementing probing-prompting could increase student activities and achievement in learning mathematic especially students in 10th grade of Kulit A SMKN 5 Yogyakarta.